2021
DOI: 10.21037/atm-21-1392
|View full text |Cite
|
Sign up to set email alerts
|

The predictive prognostic values of CBFA2T3, STX3, DENR, EGLN1, FUT4, and PCDH7 in lung cancer

Abstract: Background: Lung cancer is one of the most malignant tumors. However, neither the pathogenesis of lung cancer nor the prognosis markers are completely clear. The purpose of this study is to screen the diagnostic or prognostic markers of lung cancer.Methods: TCGA and GEO datasets were used to analyze the relationship between lung cancer-related genes and lung cancer samples. Common differential genes were screened, and a univariate Cox regression analysis was used to screen survival related genes. A univariable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Although numerous previous reports have illustrated the promotion of lung and breast cancer cell migration and invasion by PCDH7 ( Chen et al, 2021 ), the increase in this protein inhibits cell migration and invasion in gastric cancer cells. However, a recent study has shown that P7 could promote lung metastasis of colorectal cancer ( Liu et al, 2022 ), which seems contrary to our results, but we consider that this is related to different cell lines and experimental systems.…”
Section: Discussionmentioning
confidence: 85%
“…Although numerous previous reports have illustrated the promotion of lung and breast cancer cell migration and invasion by PCDH7 ( Chen et al, 2021 ), the increase in this protein inhibits cell migration and invasion in gastric cancer cells. However, a recent study has shown that P7 could promote lung metastasis of colorectal cancer ( Liu et al, 2022 ), which seems contrary to our results, but we consider that this is related to different cell lines and experimental systems.…”
Section: Discussionmentioning
confidence: 85%
“…Its roles vary. PCDH7 was defined as a risk gene, and its high expression suppressed survival in lung cancer patients in a study by Chen Y et al 29 . PCDH7 provides a potential therapeutic strategy in colon cancer: it can inhibit the MEK1/2/ERK/c-Fos axis by knocking down PCDH7, induce neurogenesis and autophagy, and enhance the effect of colon cancer cells on chemotherapy 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, using KLRG1 as a tumor antigen, APCs will be trained to recognize and remove KLRG1-expressing tumor cells and senescent immune cells, becoming a new LUAD treatment strategy. CBFA2T3 has been reported as a tumor suppressor in lung cancer and can be an independent prognostic marker in LUAD ( Zhang et al, 2018 ; Chen et al, 2021 ). Furthermore, we showed that CBFA2T3 expression was positively correlated with higher antigen-presenting cell infiltration.…”
Section: Discussionmentioning
confidence: 99%